2016
DOI: 10.4143/crt.2014.370
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Triage Strategy Based on Preoperative MRI for Avoiding Trimodality Therapy in Stage IB Cervical Cancer

Abstract: PurposeAdjuvant chemoradiation following primary surgery is frequently indicated in patients with stage IB cervical cancer. The aim of this study is to evaluate the role of a magnetic resonance imaging (MRI)-based strategy in avoiding trimodality therapy.Materials and MethodsWe retrospectively reviewed all patients with stage IB cervical cancer treated initially with primary surgery at Seoul National University Hospital. We suggest an alternative triage strategy in which the primary treatment modality is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…3Y5 Previous studies have pointed out that primary radical surgery followed by adjuvant CCRT (trimodality therapy) associated with higher toxicity and morbidity rates without significant benefit of survival than other treatment options. 4,6 Recently, some studies have suggested that inclusion of MRI in the decision-making process for primary treatment could reduce the number of patients requiring trimodality therapy based on risk factors such as pelvic lymph node metastasis or parametrial involvement (PMI). 6Y8 Although PMI is known to be an unfavourable prognostic factor for cervical cancer, few studies have investigated whether MRI-defined PMI has a significant impact on survival.…”
mentioning
confidence: 99%
“…3Y5 Previous studies have pointed out that primary radical surgery followed by adjuvant CCRT (trimodality therapy) associated with higher toxicity and morbidity rates without significant benefit of survival than other treatment options. 4,6 Recently, some studies have suggested that inclusion of MRI in the decision-making process for primary treatment could reduce the number of patients requiring trimodality therapy based on risk factors such as pelvic lymph node metastasis or parametrial involvement (PMI). 6Y8 Although PMI is known to be an unfavourable prognostic factor for cervical cancer, few studies have investigated whether MRI-defined PMI has a significant impact on survival.…”
mentioning
confidence: 99%
“…MRI is the optimal imaging modality for assessing tumor size, involvement of vaginal and peripheral tissues [ 28 , 29 ], interstitial infiltration, and lymph node metastasis in cervical cancer [ 30 ]. Implementing a preoperative MRI-based classification strategy reduces the necessity of triple therapy for stage IB cervical cancer [ 31 ]. However, the Clinic_Sig, which consists of SCC-AG, tumor size, and positive lymph nodes on MRI, exhibited subpar performance (AUC of 0.64 in the training cohort and 0.53 in the test cohort) in accurately predicting radiotherapy options for ESCSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In early cervical cancer, the positive predictive value and accuracy of MRI for detecting lymph node metastasis were reportedly 51-76% and 67-76% [7,24]. Lee et al proposed a treatment decision model based on pretreatment MRI findings [25]. Applying MRI-based treatment selection strategy to their cohort, 86 out of 254 were selected for definitive CRT instead of surgery.…”
Section: Discussionmentioning
confidence: 99%